Polyamide resin composition
A polyamide resin composition with controlled talc dispersion and specific additives addresses defects in high-talc compositions, ensuring stable mechanical properties and improved molding performance.
Patent Information
- Application Number
- JP2024173497
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-03-20
- Filing Date
- 2024-10-02
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Polyamide resin compositions with high talc content face issues such as appearance defects and sink marks due to uneven dispersion and aggregation of talc, leading to unstable mechanical properties and increased defect rates.
A polyamide resin composition characterized by specific ratios of crystalline polyamide resin and talc, with controlled average secondary particle size and the inclusion of a coupling agent and fatty acid metal salt, ensuring stable dispersion and improved mechanical properties.
The composition allows for easy molding with reduced appearance defects and sink marks, achieving consistent mechanical properties and operational stability.
Smart Images

Figure 2024174200000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyamide resin composition, and more particularly to a polyamide resin composition containing a large amount of talc as a reinforcing material. The present invention relates to a polyamide resin composition comprising: [Background technology]
[0002] The disadvantages of polyamide resin include dimensional change due to water absorption, loss of rigidity, and low heat distortion temperature. As a method to improve the quality of the material, the use of fibers such as glass fiber and carbon fiber, talc, calcium carbonate, etc. has been used for a long time. It is widely known to incorporate inorganic fillers such as rubber as reinforcing materials.
[0003] When mixing a large amount of granular inorganic filler such as talc, Since the bulk density of the filler is significantly different from that of the raw material, simple dry blending using a single screw extruder is not possible. It is difficult to mix the polyamide resin thoroughly with the coupling agent and water. By applying talc to the polyamide resin, the desired talc content can be achieved. A fat composition has been produced (for example, Patent Document 1).
[0004] However, even if the talc content is the same, the appearance of the molded product of the polyamide resin composition is different. In particular, for appearance parts, changing the molding conditions may cause defects or sink marks in the molded product. However, there is a problem that good products cannot be obtained continuously and the defect rate increases. This is the current situation. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 53-42352 Summary of the Invention [Problem to be solved by the invention]
[0006] Therefore, the present invention aims to solve the above-mentioned problems, that is, if the talc content is the same, The molded products of the polyamide resin composition have few defects in appearance and few sink marks, and have properties within the desired range. The object of the present invention is to obtain a polyamide resin composition that can be stably produced. [Means for solving the problem]
[0007] In order to solve the above problems, the present inventors have investigated the agglomeration properties of talc powder itself and the agglomeration properties of polyamide resin. We are conducting intensive research into the dispersibility of talc in aqueous solutions and the morphology of polyamide resin compositions. As a result, it was found that the dispersion and aggregation state of talc fluctuated and was not constant in some cases. By adjusting the maximum outer diameter of the talc aggregate to a specific range, the properties of the resin composition are improved. This has led to the present invention.
[0008] That is, the present invention provides [1] 50 to 90 mass% of crystalline polyamide resin (A) and 9 to 49 mass% of talc (B). % by weight of talc (B A polyamide resin composition characterized in that the average particle size of the secondary particles is greater than 30 μm. . [2] The polyamide resin composition further comprises a coupling agent (C) and a fatty acid metal salt (D ) and the polyamide resin composition according to [1]. [3] The crystalline polyamide resin (A) contains an aliphatic polyamide resin. [1] Or The polyamide resin composition according to the present invention is a polyamide resin composition according to the present invention.
[0009] The present invention makes it possible to solve the problem by adopting the above-mentioned configuration. Effect of the Invention
[0010] The polyamide resin composition of the present invention contains a large amount of talc, but is molded. Polyamide that has few defects in appearance or sink marks and stably exhibits the desired range of properties It is a resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be specifically described below. The crystalline polyamide resin (A) in the present invention has an acid amide bond (-CONH- ) and has a crystalline melting point. ) preferably contains an aliphatic polyamide resin (A1). Polyamide (Polyamide 6), Polyhexamethylene adipamide (Polyamide 66), Polytetrafluoroethylene Methylene adipamide (polyamide 46), polyhexamethylene sebacamide (polyamide 6 10), polylauryllactam (polyamide 12), poly-11-aminoundecanoic acid ( Polyamide 11), etc., and copolymers and blends of these polymers. However, the examples of the aliphatic polyamide resin (A1) and the like are not limited thereto. As the polymer, polyamide 6 and polyamide 66 are preferable, and polyamide 6 is more preferable.
[0012] The crystalline polyamide resin (A) in the present invention includes the above-mentioned aliphatic polyamide resin (A1 ), a polyamide resin (A2) that retards the crystallization of the aliphatic polyamide resin (A1) The polyamide resin (A2) is preferably an aliphatic polyamide. As long as it can delay the crystallization of the amide resin (A1), there is no particular limitation. For example, Polyamides having a higher crystallization temperature than the aliphatic polyamide resin (A1) or morphologically A polyamide that inhibits crystallization can be used. Specifically, polyamide MXD6( Polymetaxylylene adipamide), Hexamethylene terephthalate / Hexamethylene isopropyl Phthalate copolymer (6T / 6I), 4,4'-diamino-3,3'-dimethyl-disiloxane Poly(hexylenemethane) (CA) / isophthalic acid (I) / lauryllactam (LL) copolymer (I / CA / LL), and terephthalic acid (T) / trimethyl-hexamethylenediamine ( The polyamide resin (A2) may be a polymer such as a T / TMD polymer (T / TMD). Polyamide MXD6 is preferred because it can improve the appearance of molded products. MXD6 is particularly preferred because it can improve not only the appearance of molded products but also their mechanical properties. I wish.
[0013] The content ratio of the aliphatic polyamide resin (A1) and the polyamide resin (A2) is When the aliphatic polyamide resin (A) is 100 parts by mass, the aliphatic polyamide resin (A1) is 70 to 99 parts by mass. 0.5 parts by weight, and the polyamide resin (A2) is preferably 0.5 to 30 parts by weight, Aromatic polyamide resin (A1) is 80 to 95 parts by mass, polyamide resin (A2) is 5 to 20 parts by mass It is more preferable that it is a part.
[0014] The relative viscosity (96% sulfuric acid method) of the crystalline polyamide resin (A) is in the range of 1.8 to 3.5. It is preferable that the ratio is in the range of 2.0 to 3.2, and more preferable that the ratio is in the range of 2.0 to 3.2. If the ratio is less than 1.8, the toughness If the relative viscosity exceeds 3.5, the flowability tends to decrease. The same applies to the aliphatic polyamide resin (A1) and the polyamide resin (A2). When polyamide resin (A1) and polyamide resin (A2) are used in combination, the content ratio of each is The weighted average calculated from the above is regarded as the relative viscosity of the crystalline polyamide resin (A).
[0015] The amount of the crystalline polyamide resin (A) in the polyamide resin composition is 50 to 100% by weight. 90% by mass, preferably 55 to 80% by mass, more preferably 56 to 74% by mass, and even more preferably The content is preferably 60 to 68% by mass. If the content is less than 50% by mass, it is difficult to uniformly disperse the talc. Mechanical properties and other performance characteristics become unstable, and when it exceeds 90% by mass, the effect of improving impact resistance becomes small. Sai.
[0016] The talc (B) in the present invention has an average primary particle size of 1 to 20 μm. The average particle size is preferably 2 to 15 μm, and more preferably 2 to 15 μm. On the other hand, if the average particle size is less than the above range, the bending modulus and appearance of the molded product tend to decrease. The average particle size is measured by a laser diffraction method (e.g., Horiba Seisakusho Co., Ltd.). LA920W manufactured by Shimadzu Corporation) or liquid layer sedimentation type light transmission method (e.g., Shimadzu CP type, etc.) It can be calculated from the particle size value at 50% by weight of the cumulative amount read from the measured particle size cumulative distribution curve. In the present invention, the measurements were carried out by the former method.
[0017] These talcs are obtained by mechanically pulverizing naturally occurring talcs. It can be obtained by further classifying the crude oil. Mechanical crushing methods include jaw crushers and hammer crushers. -, roll crusher, screen mill, jet mill, colloid mill, roller mill The talc can be pulverized using a pulverizer such as a vibrating mill. In order to adjust the average particle size as specified in the present invention, a cyclone, a cyclone air separator, Microseparator, cyclone air separator, sharp cut separator, etc. The talc used in the present invention is produced by wet or dry classification once or repeatedly. In order to obtain talc of a certain particle size, the talc is crushed to a specific particle size and then passed through a sharp cut separator. It is preferable to carry out the classification operation using the above-mentioned method.
[0018] The talc in the present invention does not require any particular surface treatment, but it is polya In order to improve adhesion or dispersibility with mide resin, various organic titanate-based cuprates have been used. Grafting agent, organic silane coupling agent, unsaturated carboxylic acid or its anhydride Surface treatment with modified polyolefin, fatty acid, fatty acid metal salt, fatty acid ester, etc. Alternatively, a granular material obtained by granulating the material with a water-soluble polymer binder may be used. It may also be talc.
[0019] The amount of talc (B) blended (content) in the polyamide resin composition is 9 to 49 mass %, preferably is 19 to 44 mass%, more preferably 25 to 43 mass%, and further preferably 31 to 39 mass%. If it is less than 9 mass%, the effect of improving the mechanical properties is small, and if it exceeds 49 mass%, It is difficult to disperse it uniformly in the polyamide resin, and the mechanical properties and appearance of the molded product tend to become unstable. There is.
[0020] The polyamide resin composition of the present invention contains, in addition to the crystalline polyamide resin (A) and talc (B), It is preferable that the composition contains a coupling agent (C) and a fatty acid metal salt (D).
[0021] The coupling agent (C) may be a silane-based coupling agent or a titanate-based coupling agent. Agents and the like can be used. Examples of silane coupling agents include methyltrimethoxysilane and octadecyl Trimethoxysilane, Phenyltrimethoxysilane, Methacryloxypropyltrimethoxy Alkoxy-containing silanes such as silane; aminopropyltrimethoxysilane, aminopropyltrimethoxysilane, Propyltriethoxysilane, Ureidopropyltriethoxysilane, N-phenylamino Propyltrimethoxysilane, N-2-(aminoethyl)aminopropyltrimethoxysilane Aminosilane coupling agents such as silane; glycidoxypropyltrimethoxysilane, Glycidoxypropyltriethoxysilane, Glycidoxypropylmethyldiethoxysilane , glycidylbutyltrimethoxysilane, (3,4-epoxycyclohexyl)ethyl Epoxy silane coupling agents such as trimethoxysilane; mercaptopropyltrimethoxysilane; Mercaptosilane-based cuprates such as mercaptosilane, mercaptopropyltriethoxysilane, etc. Ring agent: hexamethyldisilazane, hexaphenyldisilazane, trisilazane, cyclosilazane Trisilazane, 1,1,3,3,5,5-hexamethylcyclotrisilazane, and other organosilanes Nosilazane compounds.
[0022] Examples of titanate coupling agents include tetrakis(2-ethylhexyloxy) Titanium, Titanium-i-propoxy octylene glycolate, Di-i-propoxy Titanium bis(acetylacetonate), titanium propanedioxy bis(ethylacetoacetate) tate), tri-n-butoxytitanium monostearate, di-i-propoxytitanium distearate Therlate, butyl titanate dimer, titanium octylene glycolate, diisopropanol Titanium bis(triethanolamine), titanium dihydroxy bislactate, Hydroxybis(ammonium lactate)titanium, bis(dioctylpyrophosph ester) ethylene titanate, bis(dioctyl pyrophosphate) oxyacetate Titanate, Tri-n-butoxytitanium monostearate, Tetra-n-butyltitanate , tetraisopropyl bis(dioctyl phosphite) titanate, tetraoctyl bi Tetra(ditridecylphosphite)titanate, tetra(2,2-diallyloxymethyl- 1-Butyl)bis(ditridecyl)phosphite titanate, isopropyl trioctanoate Isopropyl tricumyl phenyl titanate, Isopropyl triisosulfate Stearoyl titanate, isopropyl isostearoyl diacrylatitanate, isopropyl Pyridinemethacrylisostearoyl titanate, isopropyl tri(dioctylphosphe Titanate, Isopropyl tridodecylbenzenesulfonyl titanate, Isopropyl Pyrithris (dioctyl pyrophosphate) titanate, isopropyl tri(N-amino) diethyl-aminoethyl) titanate.
[0023] The amount of the coupling agent (C) blended (content) in the polyamide resin composition is 0.01 to 1000 μg / g. The amount is preferably 1% by mass, more preferably 0.05 to 0.8% by mass, and further preferably 0.1 The content is preferably 0.1 to 4.0% by mass relative to the talc (B). and more preferably 0.2 to 2.0 mass %.
[0024] The fatty acid metal salt (D) is used to suppress the aggregation of talc and to provide good appearance and physical properties. The fatty acid metal salt (D) is a metal salt of a fatty acid having 9 to 30 carbon atoms. For example, calcium stearate, magnesium stearate, stearic acid Zinc, calcium behenate, magnesium behenate, zinc behenate, zinc montanate, Calcium montanate, magnesium montanate, calcium melissate, magnesium melissate Nesium, Zinc melissate, Calcium cerotenate, Magnesium cerotenate, Cerotin Zinc Lignocerate, Calcium Lignocerate, Magnesium Lignocerate, Zinc Lignocerate Among these metal salts, calcium salts of fatty acids with 15 to 28 carbon atoms are The preferred salts are calcium salts, magnesium salts, or zinc salts, and particularly calcium stearate. , Magnesium stearate, Zinc stearate, Calcium behenate, Magnesium behenate Zinc behenate, zinc montanate, calcium montanate, magnesium montanate These metal salts are preferably used in combination with carboxylic acid compounds. There are synthesis methods (decomposition method) in which metal hydroxides are reacted, then washed with water, dehydrated, and dried, and synthesis methods that do not use water. It can be produced by a direct reaction method (direct method).
[0025] The amount of the fatty acid metal salt (D) in the polyamide resin composition is 0.01 to 2. % by mass, more preferably 0.05 to 1.5% by mass, and further preferably 0.1 to It is 1% by mass.
[0026] In the polyamide resin composition of the present invention, a crystalline polyamide resin (A) and talc (B ) (preferably talc having an average primary particle size of 20 μm or less) and polyamide resin (A). 50 to 90% by mass of the polyamide (A) and 9 to 49% by mass of the talc (B) are melt-kneaded together, It is necessary that the average particle size of the secondary particles of the talc (B) in the mid-resin composition is greater than 30 μm. The average secondary particle size is preferably 35 μm or more, and more preferably 40 μm or more. If the average secondary particle size is less than 30 μm, the appearance of the molded product may be poor and sink marks may occur during molding. The average particle size of the secondary particles of the talc (B) in the polyamide resin composition is 60 μm. It is preferably 50 μm or less, more preferably 50 μm or less, and even more preferably 45 μm or less.
[0027] Talc has a nucleating effect, and the polyamide resin is nucleated on the surface of the talc in the polyamide resin composition. The crystals of (B) start to form at temperatures higher than the normal crystallization temperature. When the average secondary particle size of talc is 30 μm or less, the total surface area of talc increases. The nucleating agent effect becomes prominent and the degree of crystallization increases, so the resin injected into the mold during molding also solidifies. It becomes easier to solidify before it adheres to the mold, so the mold transferability decreases and molding This not only deteriorates the product appearance, but also makes it more likely to produce sink marks because the product solidifies before the pressure can be applied. can be obtained.
[0028] The average particle size of the secondary particles is measured by injection molding a polyamide resin composition. The molded product was observed at 500x magnification using a scanning electron microscope (SEM). ) The maximum length of 500 secondary particles with a maximum length greater than the average particle size of the primary particles was measured. The average maximum length of the 100 largest secondary particles was calculated.
[0029] In addition to the above, the polyamide resin composition of the present invention may be optionally subjected to light or heat treatment within a known range. Stabilizers, antioxidants, UV absorbers, light stabilizers, plasticizers, lubricants, crystal nucleating agents, release agents, antistatic agents Inhibitors, combinations of halogen-based flame retardants and antimony trioxide, various phosphate-based flame retardants, It is also possible to add amine-based flame retardants, inorganic pigments, organic pigments, dyes, or other polymers. Yes, it is possible.
[0030] Stabilizers include hindered phenol-based antioxidants, sulfur-based antioxidants, and phosphorus-based antioxidants. Organic antioxidants such as antioxidants and heat stabilizers, hindered amines, benzophenones, etc. These include midazole-based light stabilizers, UV absorbers, metal deactivators, and copper compounds. Copper compounds include cuprous chloride, cuprous bromide, cuprous iodide, cupric chloride, and cupric bromide. , copper (II) iodide, copper (II) phosphate, copper (II) pyrophosphate, copper sulfide, copper nitrate, copper acetate, and other organic copper complexes. In addition, copper salts of carboxylic acids can be used. It is preferable that the alkali metal halide compound is contained. Examples include lithium chloride, lithium bromide, lithium iodide, sodium fluoride, and sodium chloride. Sodium, sodium bromide, sodium iodide, potassium fluoride, potassium chloride, potassium bromide These additives include potassium iodide and potassium iodide. The amount of stabilizer to be added can be selected to suit the needs of the user. It is possible to add up to 5 parts by mass per 100 parts by mass of the polyamide resin (A). .
[0031] As for flame retardants, a combination of halogen-based flame retardants and flame retardant assistants is good. Examples include brominated polystyrene, brominated polyphenylene ether, and brominated bisphenol. Epoxy polymers, brominated styrene-maleic anhydride polymers, brominated epoxy resins, bromine Brominated phenoxy resin, Decabromodiphenyl ether, Decabromobiphenyl, Brominated poly Carbonates, perchlorocyclopentadecane, and brominated crosslinked aromatic polymers are preferred. , Flame retardant assistant agents include antimony trioxide, antimony pentoxide, sodium antimonate, Zinc stannate, zinc borate, layered silicates such as montmorillonite, fluorine-based polymers, and silica Among them, from the viewpoint of thermal stability, halogen-based flame retardants such as gibbs Chromium polystyrene, flame retardant additives: antimony trioxide, sodium antimonate, tin As a non-halogen flame retardant, it is preferable to use either one of the following combinations: These include amine cyanurate, red phosphorus, metal salts of phosphinic acid, and nitrogen-containing phosphate compounds. In particular, a combination of a metal phosphinate and a nitrogen-containing phosphoric acid compound is preferred. Examples of phosphoric acid compounds include melamine and melamine condensates such as melam and melon. and polyphosphoric acid reaction products or mixtures thereof. Other flame retardants and flame retardant assistants When using these flame retardants, hydrotalcite-based compounds are used to prevent metal corrosion in molds, etc. It is preferable to add an alkali compound or an alkali compound. The amount of flame retardant to be added can be selected as the optimum amount. A maximum of 20 parts by mass can be added per 100 parts by mass of polyamide resin (A). .
[0032] The polyamide resin composition of the present invention comprises a polyamide resin (A), talc (B), a coupling agent (C), and a carboxylic acid. Coupling agent (C) and fatty acid metal salt (D) (coupling agent (C) and fatty acid metal salt (D) D) is an optional component, and preferably accounts for 85% by mass or more, and more preferably 90% by mass or more. It is more preferable that the content of the stoichiometric amount is 95% by mass or more, and further more preferable that the content of the stoichiometric amount is 95% by mass or more.
[0033] The production apparatus for producing the polyamide resin composition of the present invention is a device for dissolving polyamide resin and talc. As long as the melt-kneading can be performed, there is no particular limitation. A single screw extruder, a twin screw extruder, a kneader, etc., well known to those skilled in the art may be used. If melt mixing is possible using a Banbury mixer, roll, etc., it can be used. It is preferred to use an extruder.
[0034] The screws of twin screw extruders are full-flighted, reverse full-flighted, and straight. Alternating kneading disc, forward kneading disc and reverse kneading disc In the present invention, the screw configuration in the plasticization region is It is preferable to incorporate a kneading disk in the forward direction.
[0035] In addition, the ratio of the screw length L (mm) to the screw diameter D (mm) is L / D However, it is preferable that the relationship 10≦(L / D)≦100 is satisfied. From the viewpoint of fine dispersion of talc, it is preferable that L / D is small, if it is not more than 100. If the resin composition is heated, it tends to deteriorate due to heat, resulting in a decrease in the mechanical strength of the resin composition.
[0036] In addition, the melting temperature of the resin composition during melt kneading is preferably 180 to 330° C., It is more preferable that the melting temperature is 200 to 300° C. If the melting temperature is less than 180° C., the melting is insufficient. Conversely, if the temperature exceeds 330°C, the resin composition is susceptible to thermal degradation. It becomes easier.
[0037] The screw rotation speed N during melt kneading is preferably 100 to 1,500 rpm. The screw rotation speed is preferably 150 to 1,000 rpm. If the rpm exceeds 1,500, the talc tends to penetrate less into the resin. However, the resin is easily deteriorated due to shear heat. The discharge rate is preferably 5 to 2,000 kg / hr, and more preferably 10 to 2,000 kg / hr. If the dispersibility of talc is less than 2,000 kg / hr, the dispersibility of talc tends to decrease. If the amount exceeds this limit, the dispersibility of the talc tends to decrease due to re-aggregation of the talc.
[0038] In addition, the discharge rate Q (unit: kg / hr) and the screw rotation speed N during melt kneading (unit: rp The ratio Q / N of (Q / N) is preferably 0.01≦(Q / N)≦1, and more preferably 0.05≦(Q / N) If the ratio is less than 0.01, the mechanical strength of the resin composition is reduced due to thermal degradation. Also, if it exceeds 1, the conveying force becomes insufficient and the talc is likely to erupt. do.
[0039] In addition, talc, which is prone to poor penetration into polyamide resin during extrusion processing, is extruded in a twin-screw extruder. It is also possible to feed the material from the side of the machine. Even when the rotor is rotating at high speed, the talc penetrates the resin steadily. Talc is 3 times more effective because it comes into contact with oil and the shear with the resin pellets that occurs when the material is first loaded is reduced. It is difficult to refine the powder to less than 0 μm, and it is difficult to obtain a stable average secondary particle size of more than 30 μm. It becomes easier.
[0040] The method for producing the polyamide resin composition of the present invention comprises the steps of: When melt-kneading the talc having a secondary particle diameter of 1 to 20 μm at a predetermined ratio, It is preferable to feed a part or the whole of the talc from the side port of the twin-screw extruder. When supplying talc from the side outlet, 50% by mass or more and less than 100% by mass of the total talc amount is supplied from the side outlet. It is preferable to supply it from
[0041] In addition, the component (C) may be added at the same time as the raw materials other than talc, but it is preferable to add the talc in advance. It may also be added to the oil.
[0042] In addition, in order to remove the gas components accompanying the talc during melt kneading, the melt was In the melt-kneading section, vacuum deaeration is preferably carried out. EXAMPLES
[0043] The present invention will now be described in detail with reference to examples and comparative examples, but the present invention is not limited thereto. It is not something that is done.
[0044] The characteristics and physical properties shown in the following examples and comparative examples were measured by the following test methods.
[0045] 1) Average particle size of secondary particles of talc: The average particle size of secondary particles of talc was measured by micro-measurement using test pieces prepared as described in 4) below. Cross-sections were prepared using a chromatograph, platinum sputtered, and observed under a scanning electron microscope (S Electron Microscopy (EM) was used to observe at 500x magnification, and the maximum length was found to be greater than the average particle size of the primary particles of talc. The maximum length of 500 secondary particles with a diameter of 100 mm was measured. The average length was calculated and used as the average particle size of the secondary particles.
[0046] 2) Bending deflection rate: Measured in accordance with JIS K 7171:2016.
[0047] 3) Charpy impact strength: Measured in accordance with ISO179 / leA (notched).
[0048] 4) Appearance evaluation of molded products: Toshiba Machine EC-100 injection molding machine was used, and the cylinder temperature was The melting point of the polyamide resin is +20℃, the mold temperature is set to 90℃, the length is 100mm, the width is 100m. A test piece with a diameter of 1.0 mm and a thickness of 2 mm was prepared by injection molding. The appearance of the base was evaluated visually. ◎: There is no floating or sinking of the reinforcing material throughout the molded product. ○: There is slight lifting or sinking of the reinforcement near the gate or at the end. △: Chips are observed in small areas of the molded product. ×: There is a large amount of reinforcement lifting or sink marks throughout the molded product.
[0049] 5) Operational stability: The operational stability during melt kneading was evaluated according to the following criteria. ◎: Continuous operation is possible without talc spewing out from the inlet or vent. △: A small amount of talc sprays out from the inlet or vent. ×: A large amount of talc was ejected from the inlet and vent, making continuous operation impossible.
[0050] The raw materials used in the examples and comparative examples of the present invention are as follows. The relative viscosity (RV) of polyamide resin is measured by dissolving 0.25g of polyamide resin in 25% 96% sulfuric acid. 10 ml of this solution was placed in an Ostwald viscosity tube and measured at 20°C. (A11) Polyamide 6: Toyobo's "Glamide T-840" (RV2.2, melting point 223 °C) (A12) Polyamide 6: Ube Industries "1013B" (RV2.5, melting point 224°C) (A13) Polyamide 6: Toyobo "T-820" (RV3.1, melting point 225°C) (B1) Talc: "KST-W" manufactured by Shokozan Mining Co., Ltd. (average particle size 7 μm, apparent specific gravity 0.4) (B2) Talc: "FU-51" manufactured by Fukuoka Talc Industry Co., Ltd. (average particle size 13 μm, apparent specific gravity 0 .3) (B3) Talc: Hayashi Kasei's "KHP-400B" (average particle size 19 μm, apparent specific gravity 1.0 ) (C) Silane coupling agent: Shin-Etsu Chemical Co., Ltd.'s "KBE-903" (3-aminopropyl (triethoxysilane) (D1) Fatty acid metal salt: "NP-1500" (magnesium stearate) manufactured by Tannan Chemical (D2) Fatty acid metal salt: "CS-8CP" (calcium montanate) manufactured by Nitto Kasei Kogyo Co., Ltd. (E) Stabilizer: Potassium iodide manufactured by Mitsui Chemicals
[0051] Example 1 In order to obtain the composition shown in Table 1, the raw materials other than talc were mixed in advance and Talc was fed separately from the side feed into a twin-screw extruder (TEX5 manufactured by Japan Steel Works, Ltd.) with an L / D of 45. The mixture was fed to the melt kneading machine 4αII and melt-kneaded. After being taken out of the die in the form of a strand, The mixture is passed through a water tank to cool and solidify, and then cut into pellets using a pelletizer to produce a polyamide resin composition. The extruder barrel temperature was set at 260°C, the screw rotation speed, discharge rate, and Q The / N was set as the manufacturing conditions in Table 1. The obtained pellets were dried in a hot air dryer until the moisture content was 0.05 After drying to 0.05% or less, various properties were evaluated. The evaluation results are shown in Table 1.
[0052] Comparative Example 1 To obtain the composition shown in Table 1, the raw materials were mixed in advance and then split into two parts with a ratio of L / D45. The mixture was fed to a screw extruder (TEX54αII manufactured by Japan Steel Works, Ltd.) and melt-kneaded. After being taken out in strand form from the sinter, it is passed through a water tank to cool and solidify, and then cut into pellets by a pelletizer. The extruder barrel temperature was set at 260 The temperature, screw rotation speed, discharge amount, and Q / N were set as the manufacturing conditions shown in Table 1. The obtained pellets The samples were dried in a hot air dryer until the moisture content was reduced to 0.05% or less, and various properties were evaluated. The evaluation results are shown in Table 1.
[0053] Examples 2 to 8, Comparative Example 2 A portion of the talc was premixed with the other raw materials and supplied from the original feed under the manufacturing conditions shown in Table 1. Except for setting the temperature, pellets were prepared in the same manner as in Example 1 and evaluation was carried out.
[0054] [Table 1]
[0055] From the results in Table 1, polyamide resin and talc are contained in the specified ranges, and the average secondary particle size of talc is If the diameter is within a specified range, the polyamide resin composition has an excellent molded appearance without any floating or sink marks of the reinforcement. Furthermore, no talc is ejected during melt kneading, and the operation is stable. [Industrial Applicability]
[0056] The molded article made of the polyamide composition of the present invention has excellent appearance without any lifting of the reinforcing material or sink marks. It can be used for a wide range of applications, especially in the console, cup holder, etc. It is ideal for decorative parts where emphasis is placed on the appearance of the molded product without any floating of reinforcement or sink marks.
Claims
1. A polyamide resin composition containing 50 to 90 mass% of a crystalline polyamide resin (A) and 9 to 49 mass% of talc (B), wherein the average particle size of secondary particles of the talc (B) in the polyamide resin composition is greater than 30 μm and less than 60 μm.
2. The polyamide resin composition according to claim 1, further comprising a coupling agent (C) and a fatty acid metal salt (D).
3. The polyamide resin composition according to claim 1 or 2, wherein the crystalline polyamide resin (A) contains polyamide 6.
Citation Information
Patent Citations
Method of making resistor element for semiifixed and variable resistors
JP1978042352A
